Tolerant mechanisms to O2 deficiency under submergence conditions in plants - Nakamura, Motoka; Noguchi, Ko (Journal of plant research, 2020)
Wetland plants can tolerate long-term strict hypoxia and anoxic conditions and the subsequent re-oxidative stress compared to terrestrial plants. During O 2 deficiency, both wetland and terrestrial plants use NAD(P) + and ATP that are produced during ethanol fermentation, sucrose degradation, and major amino acid metabolisms. The oxidation of NADH by non-phosphorylating pathways in the mitochondrial respiratory chain is common in both terrestrial and wetland plants. As the wetland plants enhance and combine these traits especially in their roots, they can survive under long-term hypoxic and anoxic stresses. Wetland plants show two contrasting strategies, low O 2 escape and low O 2 quiescence strategies (LOES and LOQS, respectively). Differences between two strategies are ascribed to the different signaling networks related to phytohormones. During O 2 deficiency, LOES-type plants show several unique traits such as shoot elongation, aerenchyma formation and leaf acclimation, whereas the LOQS-type plants cease their growth and save carbohydrate reserves. Many wetland plants utilize NH 4 + as the nitrogen (N) source without NH 4 + -dependent respiratory increase, leading to efficient respiratory O 2 consumption in roots. In contrast, some wetland plants with high O 2 supply system efficiently use NO 3 − from the soil where nitrification occurs. The differences in the N utilization strategies relate to the different systems of anaerobic ATP production, the NO 2 − -driven ATP production and fermentation. The different N utilization strategies are functionally related to the hypoxia or anoxia tolerance in the wetland plants.